2021
DOI: 10.1111/lam.13536
|View full text |Cite
|
Sign up to set email alerts
|

Comparative immunogenicity of outer membrane protein K and whole‐cell antigens of Vibrio parahaemolyticus for diagnosis

Abstract: The immunogenicity of soluble outer membrane protein K (OmpK)‐ small ubiquitin‐like modifier, OmpK inclusion bodies, formalin, and heat‐killed Vibrio parahaemolyticus cells were prepared and studied in a mouse model. The results of whole‐cell ELISA and Western blot (WB) revealed that the serum against soluble OmpK and OmpK inclusion bodies reacted only with homologous V. parahaemolyticus. Furthermore, recombinant OmpK proteins were not recognized by the serum against whole‐cell V. parahaemolyticus antigens. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…But the synthesis of the OmpU protein is regulated by NaCl content of the cultured medium, OmpU accounts for 30% of the total outer membrane protein when V. cholerae cultured in 1.0% NaCl medium and 60% in without NaCl [ 39 ]. Besides, the outer membrane protein OmpK with nucleoside transmembrane transport protein activity is highly conserved in Vibrio , which has been recognized [ 41 ]. There have some proteins with efflux transmembrane transporter activity also conserved in various NaCl stress cultured, such as outer membrane channel protein ( tolC ), outer membrane protein ( VIBR0546_13282 ), and outer membrane protein ( VIBR0546_20323 ) that have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…But the synthesis of the OmpU protein is regulated by NaCl content of the cultured medium, OmpU accounts for 30% of the total outer membrane protein when V. cholerae cultured in 1.0% NaCl medium and 60% in without NaCl [ 39 ]. Besides, the outer membrane protein OmpK with nucleoside transmembrane transport protein activity is highly conserved in Vibrio , which has been recognized [ 41 ]. There have some proteins with efflux transmembrane transporter activity also conserved in various NaCl stress cultured, such as outer membrane channel protein ( tolC ), outer membrane protein ( VIBR0546_13282 ), and outer membrane protein ( VIBR0546_20323 ) that have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in a study using recombinant OmpK, recombinant GAPDH, and a fusion of both antigens as possible vaccines, although antibody titration from vaccinated groups was significantly different from the control group, the protective effect upon challenge was better using the fusion of both antigens ( 88 ). In another study ( 89 ), serum from mice immunized with recombinant OmpK from V. parahaemolyticus only reacted with homologous V. parahaemolyticus , indicating that recombinant OmpK may not be the ideal target antigen for the development of a polyvalent vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A study on cross-protection also found a recombinant cell vaccine had successfully induced an immune response to V. parahaemolyticus in juvenile sea bass by expressing the OmpK of Vibrio [ 27 ]. At the same time, another study has pointed out the limitation of recombinant OmpK in preparing diagnostic antibodies [ 44 ]. For this reason, using modern methods for understanding and developing new V. parahaemolyticus immunogenic proteins and antibodies are necessary [ 45 , 46 ].…”
Section: Control and Prevention Strategies Of Vibriosmentioning
confidence: 99%